2015
DOI: 10.1016/j.neulet.2015.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein response is activated in aged retinas

Abstract: An unfolded protein response (UPR) in addition to oxidative stress and the inflammatory response is known to be activated in age-related ocular disorders, such as macular degeneration, diabetic retinopathy, glaucoma, and cataracts. Therefore, we aimed to investigate whether healthy aged retinas display UPR hallmarks, in order to establish a baseline for the activated UPR markers for age-related ocular diseases. Using western blotting, we determined that the hallmarks of the UPR PERK arm, phosphorylated (p) eIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 41 publications
2
13
0
1
Order By: Relevance
“…Of interest, gene expression profile studies demonstrated that UPR‐target genes are one of the most affected pathways in bone marrow during aging (Kannan et al ., ). At the level of the central nervous system, phosphorylation of CHOP, ATF6, GADD34, ATF4, and eIF2α are also upregulated in the retina of aged rats (Lenox et al ., ).…”
Section: Er Stress Response In Mammalian Agingmentioning
confidence: 97%
“…Of interest, gene expression profile studies demonstrated that UPR‐target genes are one of the most affected pathways in bone marrow during aging (Kannan et al ., ). At the level of the central nervous system, phosphorylation of CHOP, ATF6, GADD34, ATF4, and eIF2α are also upregulated in the retina of aged rats (Lenox et al ., ).…”
Section: Er Stress Response In Mammalian Agingmentioning
confidence: 97%
“…Several studies have revealed that the age-related tissue atrophy and degeneration are associated with a decline in the amounts of many UPR-related transducers and chaperones, whereas the expression of ER stress linked CHOP was significantly increased with aging, e.g., in mouse cerebral cortex [48] and adipose tissues [49] as well as in the skeletal muscles [50], liver [51], and retina [52] of rats. CHOP is not only associated with apoptosis, it performs many immune and metabolic responses as well as having effects on adipocyte and osteoblast differentiation [53].…”
Section: Er Stress In the Aging Processmentioning
confidence: 99%
“…There are several limitations that should be addressed. For example, the unfolded protein response not only occurs neurodegenerative disorders, but is also activated as a part of the normal aging process, which is marked by an increase in oxidative stress and the pro-inflammatory state (Lenox et al, 2015). Jackson et al hypothesized that aging results in disturbance of the visual cycle responsible for rhodopsin regeneration.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%